Supination adduction stage 2 associated with transverse fracture of the lateral malleolus and rupture of the anterior talofibular ligament: a case report and literature review - Wang, Jingxuan; Yang, Kangyong; Liu, Zhenjiang; Jie, Ke; Huang, Biqing; Wang, Shiheng; Mo, Zhihong; Zou, Yunxuan (Frontiers in Surgery, 2025)
BackgroundSupination-adduction (SAD) type ankle fractures occur when the ankle is subjected to inversion forces while in a supinated position, leading to transverse fractures of the lateral malleolus or lateral ligament injuries, often accompanied by vertical fractures of the medial malleolus. Unlike the typical SAD pattern, the concurrent occurrence of a transverse lateral malleolus fracture combined with rupture of the Anterior Talofibular Ligament (ATFL) is uncommon and has not been reported in the literature; such injuries are frequently missed in clinical practice, which in turn affects clinicians’ treatment decisions and the recovery of ankle joint stability and function.Case presentationThis report describes a case of an adult Asian female patient who sustained a left ankle injury due to a missed step, resulting in swelling and pain. The initial diagnosis was a left double ankle fracture (SAD stage 2). During surgery, after stabilizing the medial and lateral malleoli, fluoroscopy revealed that the talus could not be reduced. An extended incision identified the ATFL rupture, which was subsequently repaired using the Broström-Gould technique. Post-repair fluoroscopy confirmed satisfactory reduction of the talus and proper alignment of the ankle joint. After two weeks of cast immobilization, the patient began gradual rehabilitation exercises. At the 18-month follow-up, the patient exhibited good ankle function, achieving an American Orthopaedic Foot and Ankle Society Ankle - Hindfoot Scale of 100.ConclusionThis report shares the clinical experience in diagnosing and treating occult injuries of the ATFL in a case of SAD stage 2 ankle fracture to enhance awareness and prevent missed diagnoses in similar injuries. We emphasize that in SAD stage 2 fractures showing unexplained talar tilt after fixation, clinicians should suspect and evaluate for occult ATFL injury to avoid missed diagnoses and optimize treatment decisions.